Cervical diseases after subtotal hysterectomy (modern aspects of diagnosis and tactics of management) - Albina Kh. Karanasheva; Yulia E. Dobrokhotova (IP Berlin A.V., 2021)
Aim. To study the state of the cervical stump after subtotal hysterectomy (STGE) without uterine appendages with and without excision of the endocervix in patients with myoma to justify the choice of a rational volume of surgical operation. Materials and methods. Examination and treatment of 140 women was carried out with the formation of three groups: 1st 40 patients after laparoscopic STGE with excision of the endocervix; 2nd 38 patients after laparoscopic STGE without excision of the endocervix; 3rd (comparison group) 62 patients with uterine myoma that do not require surgical treatment. Results. The study of the state of the cervical stump was carried out 5.10.3 years after surgery. The number of patients with cervical pathology after STGE with excision of the endocervix (in group 1) was 1.8 times less in percentage terms than after STGE without excision of the endocervix (in group 2), and 3.2 times less than in patients with uterine fibroids who do not require surgical treatment (in the 3rd comparison group). Conclusion. Out of 3 (3.8%) patients after surgical treatment with diagnosed HPV type 16.1 (1.3%) in the STGE group without endocervical excision was diagnosed with grade II intraepithelial neoplasia (CIN II). In patients with uterine myoma, STGE can be performed only after a comprehensive preoperative examination, including: diagnosis and treatment of urogenital infections, DNA typing of HPV of high oncogenic types, cytological and colposcopic examination of the cervix, targeted biopsy of the cervix with histological examination of the material. If a subtotal hysterectomy is performed, it must be supplemented with excision of the endocervix. In the future, these women require careful follow-up to improve early diagnosis and treatment of underlying and precancerous diseases and reduce the risk of developing cervical stump cancer.